A Membrane-Free and Practical Mixed Electrolyte Direct Borohydride Fuel Cell. Issue 3 (1st January 2016) - Grimmer, Christoph; Zacharias, Robert; Grandi, Maximilian; Pichler, Birgit; Kaltenboeck, Ilena; Gebetsroither, Florian; Wagner, Julian; Cermenek, Bernd; Weinberger, Stephan; Schenk, Alexander; Hacker, Viktor
Abstract : A membrane-free direct borohydride fuel cell that is operated with a borohydride containing electrolyte is designed and constructed. Main focus of this study is the cathode catalyst that has to show high tolerance against borohydride. Both catalysts, Ag-Mn3 O4 /C as cathode catalyst and commercial Pt/C as anode catalyst, are characterized electrochemically using a rotating disk electrode. The number of exchanged electrons is calculated employing Levich and Koutecky-Levich analysis. Cathodes are fabricated using a cross rolling method with an in-house made gas diffusion layer. A cell with an implemented Luggin capillary is designed in order to follow the electrode potentials. The BH4 − /O2 fuel cell shows a power density of 17 mW cm −2 using a 1 M NaBH4 /1 M NaOH/5 mM thiourea electrolyte.